Pengaruh Membatik Menggunakan Bahan Alam terhadap Motorik Halus Anak di Taman Kanak-Kanak Miftahul Jannah Padang - Sinthia Oktama Idris; Farida Mayar (Lembaga Yasin AlSys, 2026)
The low level of fine motor development in early childhood, evident in suboptimal abilities to hold writing tools, cut, paste, and perform accurate eye–hand coordination, remains a classroom challenge due to learning activities that tend to be monotonous and lack variation. This study aimed to determine the effect of batik activities using natural materials on the fine motor development of young children. A quantitative approach was employed with a quasi-experimental design, using fine motor skill tests as the data collection technique and data analysis conducted with a t-test using SPSS version 26. The results showed that children’s fine motor skills in the experimental class improved more than those in the control class. The t-test yielded a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Thus, batik activities using natural materials have a significant effect on the fine motor development of young children and can be recommended as a varied and meaningful alternative learning activity to support fine motor stimulation in PAUD institutions.